Extracellular Vesicles from Neurosurgical Aspirates Identifies Chaperonin Containing TCP1 Subunit 6A as a Potential Glioblastoma Biomarker with Prognostic Significance. Issue 1 (24th January 2019) - Hallal, Susannah; Russell, Benjamin P.; Wei, Heng; Lee, Maggie Yuk T.; Toon, Christopher W.; Sy, Joanne; Shivalingam, Brindha; Buckland, Michael E.; Kaufman, Kimberley L.
Abstract: Glioblastoma, WHO‐grade IV glioma, carries a dismal prognosis owing to its infiltrative growth and limited treatment options. Glioblastoma‐derived extracellular vesicles (EVs; 30–1000 nm membranous particles) influence the microenvironment to mediate tumor aggressiveness and carry oncogenic cargo across the blood–brain barrier into the circulation. As such, EVs are biomarker reservoirs with enormous potential for assessing glioblastoma tumors in situ. Neurosurgical aspirates are rich sources of EVs, isolated directly from glioma microenvironments. EV proteomes enriched from glioblastoma ( n = 15) and glioma grade II–III ( n = 7) aspirates are compared and 298 differentially‐abundant proteins ( p‐ value < 0.00496) are identified using quantitative LC–MS/MS. Along with previously reported glioblastoma‐associated biomarkers, levels of all eight subunits of the key molecular chaperone, T‐complex protein 1 Ring complex (TRiC), are higher in glioblastoma‐EVs, including CCT2, CCT3, CCT5, CCT6A, CCT7, and TCP1 ( p  < 0.00496). Analogous increases in TRiC transcript levels and DNA copy numbers are detected in silico; CCT6A has the greatest induction of expression and amplification in glioblastoma and shows a negative association with survival ( p = 0.006). CCT6A is co‐localized with EGFR at 7p11.2, with a strong tendency for co‐amplification ( p  < 0.001). Immunohistochemistry corroborates the CCT6A proteomics measurements and indicated a potential link between EGFR and CCT6A tissue expression. Putative EV‐biomarkers described here should be further assessed in peripheral blood.